Lard intake results in better hypothalamic leptin responsiveness than beef tallow intake during overnutrition - Mutsumi Ikeda; Tamae Shiino; Kai Naruke; Nozomi Takahashi; Hanako Kanzaki; Ran Xu; Toshimi Shirozu; Misato Nakano; Miharu Murae; Yui Funatsu; Kentaro Kaneko (PLoS ONE, 2025)
The hypothalamus helps regulate energy homeostasis, but high-fat diet intake leads to body weight gain and diminishes hypothalamic responses to metabolic hormones such as leptin. The fatty acid compositions of beef tallow and lard, which are representative animal fats in experimental diets, are similar. However, it is not clear how differences in the effects of obesogenic conditions induced by the intake of beef tallow or lard affect hypothalamic leptin responsiveness. Herein, we showed that under obesogenic conditions as 45 kcal% fat, lard-fed mice had lower body weight gain, food intake, respiratory quotient, and adiposity and better glucose balance and insulin sensitivity than beef tallow-fed mice. Furthermore, the central administration of leptin reduced body weight and food intake in mice fed lard, but not beef tallow, under the same overnutrition conditions. Lard-fed mice also exhibited lower levels of hypothalamic suppressor of cytokine signaling-3, an inhibitor of leptin activity, than mice fed beef tallow. While there were no differences in body weight with the low-fat diet as 30 kcal% fat, central leptin-induced body weight and food intake reductions in lard were higher than those in beef tallow. Finally, we showed that leptin-deficient ob/ob mice, another mouse model of obesity, did not show any improvement in energy balance under lard-fed conditions. Our results showed that lard was better than beef tallow in maintaining hypothalamic leptin responsiveness and systemic metabolic states under obesogenic conditions.